2022
DOI: 10.4266/acc.2021.00920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of critically ill COVID-19 and influenza patients with acute respiratory failure

Abstract: Background: Coronavirus disease 2019 (COVID-19) is one of the biggest pandemic causing acute respiratory failure (ARF) in the last century. Seasonal influenza carries high mortality, as well. The aim of this study was to compare features and outcomes of critically-ill COVID-19 and influenza patients with ARF. Methods: Patients with COVID-19 and influenza admitted to intensive care unit with ARF were retrospectively analyzed. Results: Fifty-four COVID-19 and 55 influenza patients with ARF were studied. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…All studies were retrospective cohort studies. Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were retrospective cohort studies. Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in the United States ( 18 , 19 , 21 , 23 , 24 ), two in China ( 27 , 29 ), one in France ( 20 ), one in Austria ( 22 ), one in Turkey ( 25 ), one in Israel ( 26 ), and one in Pakistan ( 28 ). Eight studies ( 18 , 19 , 22–24 , 26 , 28 , 29 ) reported data on general hospitalized patients, and four studies reported data on critically ill patients in ICUs ( 20 , 21 , 25 , 27 ) and patients with ARDS requiring veno-venous ECMO ( 20 ). Three studies ( 27–29 ) enrolled patients with H1N1 (subtype of influenza A), six studies ( 20–24 , 26 ) enrolled patients with type A or B influenza, while the other four studies ( 18 , 19 , 24 , 25 ) recruited influenza patients without mentioning the subtype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations